(untitled) (Research, Society and Development, 2022)
The Brazilian Unified Health System (in portuguese, Sistema Único de Saúde – SUS) stands out worldwide for the free coverage that provides comprehensive and quality care support for patients with chronic kidney disease, who are often directed to the transplant list as an eligible resource in the last instance of treatment. The Brazil’s National Transplant System is known worldwide for having a effective planning, logistics, drug treatment and follow-up for these patients. In the post-transplant phase, the individuals require treatment with immunosuppressive drugs such as azathioprine, cyclosporine, tacrolimus and prednisone, which are provided in their entirety by Ministry of Health programs in order to prevent organ rejection. An analysis among the therapeutic options available on the market shows that, among the prescribed drugs, the best cost-benefit with increased survival was observed in patients using azathioprine, prednisone and tacrolimone regimen so far as cyclosporine was the most widespread choice option previously. In an analysis of costs generated with the surgical process, multidisciplinary clinical follow-up and continuous treatment after transplantation are measured through databases that have pre-fixed values and are used to survey the values added to the care of each patient, in which it is later billed and passed on to the institutions. Regarding treatment, the receivers have a better quality of life with the use of the therapeutic regimen with tacrolimin in maintenance therapy reducing the chances of readmission.